1997
DOI: 10.1007/bf03401683
|View full text |Cite
|
Sign up to set email alerts
|

Priming of Cytotoxic T Lymphocytes by DNA Vaccines: Requirement for Professional Antigen Presenting Cells and Evidence for Antigen Transfer from Myocytes

Abstract: Upon injection of NP DNA, or after infection with influenza virus, CTL responses generated in the chimeras were restricted to the donor MHC haplotype. Thus cells of BM lineage were definitively shown to be responsible for priming such CTL responses after infection or DNA immunization. Moreover, expression of antigen by muscle cells in BM chimeric mice after myoblast transplantation is sufficient to induce CTL restricted only by the MHC haplotype of the donor BM. This indicates that transfer of antigen from myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
145
0
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(151 citation statements)
references
References 31 publications
3
145
0
3
Order By: Relevance
“…This hypothesis would be in accordance with the observations by others reporting that the induction of apoptosis significantly promotes the stimulation of immune responses towards per definition cytoplasmic antigens [37,38]. Accordingly, there is clear evidence suggesting that the induction of CTL and IFN-␥ producing T cells may be supported in all cases-and independent from our in vitro findings demonstrating cytoplasmic location of GagMyr − and p24-by cross-priming events via antigens in vivo [21,39]. Due to the leakyness of transduced cells regarding the release of otherwise cytosolic antigens, genetic strategies that aim to target Gag-derived antigens to the cytosolic compartment or, in the contrary, supporting the release from cells are not suited to quantify the contribution of cross-priming to the generation of cell mediated immune responses.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This hypothesis would be in accordance with the observations by others reporting that the induction of apoptosis significantly promotes the stimulation of immune responses towards per definition cytoplasmic antigens [37,38]. Accordingly, there is clear evidence suggesting that the induction of CTL and IFN-␥ producing T cells may be supported in all cases-and independent from our in vitro findings demonstrating cytoplasmic location of GagMyr − and p24-by cross-priming events via antigens in vivo [21,39]. Due to the leakyness of transduced cells regarding the release of otherwise cytosolic antigens, genetic strategies that aim to target Gag-derived antigens to the cytosolic compartment or, in the contrary, supporting the release from cells are not suited to quantify the contribution of cross-priming to the generation of cell mediated immune responses.…”
Section: Discussionsupporting
confidence: 93%
“…Such APCs have been suggested to be directly transfected leading to endogenous protein synthesis and engagement of the MHC class I and II processing and presentation pathway [18,19]. Alternatively, in the context of 'cross-priming' APC may incorporate and process extracellular proteins, which have been produced and secreted by muscle cells [20][21][22]. This contrasts a previous dogma stating that exogenous proteins are almost exclusively degraded via the MHC class II processing and presentation pathway.…”
Section: Introductionmentioning
confidence: 99%
“…However, only few bone marrow-derived antigen-presenting cells (APCs), 3,4 especially dendritic cells (DCs) that perform a critical step in the induction of primary immune responses, are directly transfected by injected DNA, 5,6 leading to deficient presentation of peptides from endogenously synthesized antigens on major histocompatibility complex (MHC) molecules. Studies of stably transfected myoblasts, [7][8][9] reconstitution of SCID mice with allogeneic bone marrow-derived APCs after DNA vaccination, 4 and surgical ablation of the injection site, 10 as well as skin excision/grafting experiments 11 also indicate a role for transfected myocytes and keratinocytes in DNA-initiated immune responses. However, these studies demonstrate that acquisition of antigens released from transfected myocytes or keratinocytes and cross-presentation by DCs are essential to induce T-cell responses for any DNA vaccination strategy.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was subsequently shown that only professional antigen-presenting cells (APC) could actually prime immune responses with DNA vaccines. [7][8][9][10] While direct transfection of APC is not absolutely essential, 11 it is probable that some APC are transfected and antigen expression in these APC primes MHC class I and II responses. This may account for the strong immune responses induced by DNA vaccines, especially considering the extremely small quantities of antigen expressed from typical doses of plasmid DNA.…”
Section: Introductionmentioning
confidence: 99%